When gods speak to men (Leuven ; Paris ; Bristol, CT)
x, 138 sayfa
Keywords: “The nature of divine speech in Antiquity in the Mediterranean Basin has often been the object of scholarly analysis, especially regarding its divinatory context and questions of genre and rhetoric. The present volume not only provokes a dialogue with this past research, but seeks to respond to a problem that has received little consideration until now: the articulation of divine speech with the various forms of its representation (linguistic, literary, and material). The aim is to analyze the nature of divine speech through its materiality and the impact of the latter on the former's definition and evolution.” --